Embedded Platforms for UAS Landing Path and Obstacle Detection II Navigation Support Systems for Urban Air Mobility Operations - Ariante, Gennaro; Papa, Umberto (Studies in Systems, Decision and Control, 2024)
XXVI, 114 p. 88 illus., 84 illus. in color.